Mentors' perspectives on strengths and weaknesses of a novel clinical mentorship programme in Rwanda: a qualitative study. Issue 3 (19th March 2021) - Uwisanze, Sandrine; Ngabonzima, Anaclet; Bazirete, Oliva; Hategeka, Celestin; Kenyon, Cynthia; Asingizwe, Domina; Kanazayire, Clementine; Cechetto, David
Abstract : Objectives: To identify mentors' perspectives on strengths and weaknesses of the Training, Support and Access Model for Maternal, Newborn and Child Health (TSAM-MNCH) clinical mentorship programme in Rwandan district hospitals. Understanding the perspectives of mentors involved in this programme can aid in the improvement of its implementation. Design: The study used a qualitative approach with in-depth interviews. Setting: Mentors of TSAM-MNCH clinical mentorship programme mentoring health professionals at district hospitals of Rwanda. Participants: 14 TSAM mentors who had at least completed six mentorship visits on a regular basis in three selected district hospitals. Results: Mentors' accounts demonstrated an appreciation of the two mentoring structures which are interprofessional collaboration and training. These structures are highlighted as the strengths of the mentoring programme and they play a significant role in the successful implementation of the mentorship model. Inconsistency of mentoring activities and lack of resources emerged as major weaknesses of the clinical mentorship programme which could hinder the effectiveness of the mentoring scheme. Conclusion: The findings of this study highlight the strengths and weaknesses perceived by mentors of the TSAM-MNCH clinical mentorship programme, providing insights that can be used to improve its implementation. The study represents unique TSAM-MNCH structural settings, but its findings shed light on Rwandan health system issues that need to be further addressed to ensure better quality of care for mothers, newborns and children.